2013
DOI: 10.1177/000348941312200710
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dexpanthenol for Pediatric Post-Tonsillectomy Pain and Wound Healing

Abstract: Postoperative administration of dexpanthenol significantly accelerates the wound healing process and decreases tonsillectomy-related pain complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
0
19
1
1
Order By: Relevance
“…The topical application of dexpanthenol is widely used to stimulate skin regeneration and promote wound healing (10,22). It is also used to manage post-tonsillectomy pain and mucosal healing (23). Although rapid wound closure was expected because of the dexpanthenol (9) found in the Oral-norm gel, in the present study, no statistically significant differences were observed in the wound width or mean wound surface area.…”
Section: Discussioncontrasting
confidence: 48%
“…The topical application of dexpanthenol is widely used to stimulate skin regeneration and promote wound healing (10,22). It is also used to manage post-tonsillectomy pain and mucosal healing (23). Although rapid wound closure was expected because of the dexpanthenol (9) found in the Oral-norm gel, in the present study, no statistically significant differences were observed in the wound width or mean wound surface area.…”
Section: Discussioncontrasting
confidence: 48%
“…In a double-blind RCT, the potential of a dexpanthenol pastille containing 100 mg dexpanthenol was evaluated to alleviate pain and to improve wound healing following tonsillectomy (69). In total, 120 pediatric patients were randomized to one of four groups (N ¼ 30 each): surgical tonsillectomy technique 1 plus dexpanthenol pastille or placebo, or surgical tonsillectomy technique 2 plus dexpanthenol pastille or placebo.…”
Section: Postoperative Usementioning
confidence: 99%
“…The group that took dexpanthenol suffered less pain than the placebo group, and wound healing was accelerated (26). …”
Section: Discussionmentioning
confidence: 99%